Primary Renal Sarcomas With BCOR-CCNB3 Gene Fusion: A Report of 2 Cases Showing Histologic Overlap With Clear Cell Sarcoma of Kidney, Suggesting Further Link Between BCOR-related Sarcomas of the Kidney and Soft Tissues. (December 2017) - Argani, Pedram; Kao, Yu-Chien; Zhang, Lei; Bacchi, Carlos; Matoso, Andres; Alaggio, Rita; Epstein, Jonathan I.; Antonescu, Cristina R.
Abstract : We report 2 primary renal sarcomas demonstrating BCOR-CCNB3 gene fusions that have recently been identified in undifferentiated round cell sarcomas of bone and soft tissue. These neoplasms occurred in male children aged 11 and 12 years, and both were cystic as a result of entrapment and dilatation of native renal tubules. Both cases were composed of variably cellular bland spindle cells with fine chromatin set in myxoid stroma and separated by a branching capillary vasculature. Both neoplasms demonstrated immunoreactivity for BCOR, cyclin D1, TLE1, and SATB2 in the spindle neoplastic cells and negativity in the prominent capillary vasculature. One case was extensively cystic and had hypocellular areas that simulated cystic nephroma; this neoplasm recurred 3 years later as a solid, highly cellular spindle cell sarcoma in the abdominal cavity. The morphology and immunoprofile of these renal neoplasms was compared with a control group of other sarcomas with BCOR genetic abnormalities, including clear cell sarcoma of the kidney (CCSK), infantile undifferentiated round cell sarcomas of soft tissue/primitive myxoid mesenchymal tumor of infancy, and bone/soft tissue sarcomas with BCOR-CCNB3 gene fusion; along with primary renal synovial sarcoma. Our findings show that the renal sarcomas with BCOR-CCNB3 gene fusion overlap with CCSK. These results are in keeping with a " BCOR- alteration family" of renal and extrarenal neoplasms which includes CCSK and undifferentiated round cell sarcomas of soft tissue/primitive myxoid mesenchymal tumor of infancy (which typically harbor BCOR internal tandem duplication), and BCOR-CCNB3 sarcomas, all of which are primarily driven by BCOR overexpression and have overlapping (but not identical) clinicopathologic features. Abstract : Supplemental Digital Content is available in the text.